A Chronicle of Bosnian Turkology: The Franciscans and the Turkich Language - Čaušević, Ekrem (2004)
In the contex of the once dominant ideological discourse of former Yugoslavia, the various confessions and cultures in Bosnia and Herzegovina during the Ottoman period are as a rule presented in the rosy light of the age-old tolerance of fraternal nations. The antipodes of this was the no less ideologized view of two different worlds, the Christian and the Muslim, divided by hatred. As usual, the truth probably lies somewhere between the two: the daily lives, political views and confessional world-views of the common people of Bosnia was certainly not permeated and filled with all-ebmarcing harmony and tolerance, but neither did they exist side by side as autistic, distinct worlds, deaf to one another. To pause for a moment on just one aspects of those inevitable two-way influences, this capter begins with the claim that the Franciscans of Bosnia and Herzegovina - by a concatenation of circumstances, certainly - sowed the first seeds of linguistic Turkology in Bosnia and Herzegovina, and that the significance of their manuscripts on the Turkish language for the cultural history of this part of the world, in particular, and for linguistic Turkology, in general, is indeed respectable. Indeed, the very fact that these works originate from an area that once had a purely oriental, Islamic world view is in itself unusual and interesting.
Projekt MZOS
ENG